Simulation of spatial strain inhomogeneities in lithium-ion-cells due to electrode dilation dependent on internal and external cell structures. (May 2022) - Ebert, Fabian; Spielbauer, Markus; Bruckmoser, Maximilian; Lienkamp, Markus
Highlights: LIB format dependent material layer strain due to electrode dilation is observed. Pouch-type cells show the lowest and homogeneous strain pattern of all cell types. Module bracing leads to significantly altered material layer strain in LIB. Implementation of a elastomer layer mitigates and homogenizes layer strain in LIB. Study of an optimized stacked hardcase-type LIB with elastomer layer is presented. Abstract: Electrochemical-mechanical interactions, especially pressure-induced ones, have been identified to be a cause for lithium-plating in lithium-ion cells. Mechanically induced porosity inhomogeneities in the separator layers due to electrode expansion during charging especially lead to cell internal balancing currents and can cause localized plating. To identify cell-format and cell-material dependent mechanical weak spots, a layer-resolved mechanical simulation of different cell types and cell-material combinations is presented in this work. The simulation results show distinctive layer strain patterns for different cell-types that coincide with localized lithium-plating found in post-mortem cells. Additionally, the effects of cell bracing in battery modules is investigated and a method to mitigate the increased layer strain due to bracing counterforces is proposed that also increases cell energy density for hardcase-type automotive cells.